A review on the evaluating the influence of employment nano-matekaolin and additive materials on the improvement of hot mixture asphalt properties - Naba Sabah Radhi,; Ali Fadhil Naser,; Mohammed Kareem Abed,
In previous years, the world witnessed great urban development which increased interest in this aspect. To keep pace with this development, several things and new materials have been created to raise the standard of road construction. One of these things is the use of nanomaterials. Currently, the use of nanomaterials has become common to improve the asphalt mixtures which are used in the construction of flexible pavement because of the rise in traffic volumes and vehicles loads. This study deals with review of past related studies that improving the properties of asphalt mixtures through the use of nanometakaoline in the hot asphalt mixture in different proportions. Different proportions of nanometakaoline were used for the Hot Mixture Asphalt properties revised in these studies which were shown that the adding of nano-metakaoline led to improve the properties of Hot Mixture Asphalt to resist the traffic load and environmental effects. They used Marshall Test, indirect test, wheel track tests and others tests to exam the properties of improved Hot Mixture Asphalt and compared with the standard mixture (control).